Respuesta :
no its not a function :)
to find the inverse function first expand those brackets
you'll get
f(x)= x^2 - 2x^2 - 2x^2 = 4x^2
f(x)= x^2 - 4x^2 + 4x^2
f(x)= x^2 or y=x^2
to find the inverse, swap x and y around. then make y the subject again
y=x^2
x=y^2
Root of x=y
now put -1 into x
it wont work because roots cannot have negative numbers
answer is no
to find the inverse function first expand those brackets
you'll get
f(x)= x^2 - 2x^2 - 2x^2 = 4x^2
f(x)= x^2 - 4x^2 + 4x^2
f(x)= x^2 or y=x^2
to find the inverse, swap x and y around. then make y the subject again
y=x^2
x=y^2
Root of x=y
now put -1 into x
it wont work because roots cannot have negative numbers
answer is no